Supervision practices for foreign graduate research students - Zainal Abiddin, Norhasni; West, Mel (Science Publications, 2007)
Past research had shown that only highly unusual graduate research students had successfully completed their research degree programmes while the relationship with their supervisors was poor. There were many factors that had contributed to poor achievement of foreign students and one of the most important critical factors found which contributed to this problem was the weaknesses in supervision they received. This research was to identify the type and level of support given to foreign graduate research students by their supervisors as well as schools/universities. This research was using the quantitative method where the data was collected using on-line questionnaires. As many as 110 foreign Ph.D. students from 45 well-established universities in the United Kingdom were involved in this study. This research managed to expose what the students had expected and what they have received from the supervisor and school. As a result, the research had developed better practices and guidelines for student, supervisor and school.